Solidarity Economy and Migrations - Esteves, A. (Guest Lecture at the University of Florence, 2021)
Solidarity Economy (SE) Refers to emerging local and regional movements that are organizing community-based economic projects in webs of mutual recognition and support, aimed at building a democratic alternative to the economic orthodoxy (Miller 2013). envisions a plural economic space that fully acknowledges and supports practices based on “non-contractual, nonutilitarian solidarity” (Laville and Eynaud, 2019, p. 61), such as those based on reciprocity, redistribution and householding (Lucas dos Santos and Bannerjee, 2019). It also promotes the economic and ecological resilience of territories through the re-territorialization of economic activity (Laville 2016). The core goal of SE is to redefine the economic space by upscaling, giving visibility and promoting the institutional recognition of non-capitalist forms of work and organization that, although ubiquitous in the everyday life, have been marginalized from theory and policy by the dominant neoclassical paradigm (Gibson-Graham 1996). SE and integration of migrants(UNIRISD Research and Policy Brief 31, October 2020) SE organizations (SEOs), being more democratic and inclusive than the private sector, facilitate the participation of migrants and refugees. Many organizations which were already offering social services to vulnerable people in their locality extended their services to migrants and refugees when the number of arrivals increased. Many SEOs are created by migrants and refugees themselves.